PENDAMPINGAN PENYUSUNAN LAPORAN LABA RUGI USAHA MIKRO KECIL MENENGAH (UMKM) PADA PABRIK TAHU APOH - Yuliyati; Herlina; Nurlaelah; Susana Dewi; Hanifah; Ria Lusiana; Ahmad Wahid Murniawan, (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2021)
Micro, Small and Medium Enterprises (MSMEs) must carry out systematic recording or bookkeeping of transactions that occur every day. Transaction recording generally uses an accounting system. The function of accounting is to present financial information to internal and external parties and as a basis for making decisions. In this case, MSMEs also need financial reports which aim to present information regarding the financial position, budget realization, cash flow and financial performance of a reporting entity which is useful for users in making and evaluating decisions regarding resource allocation. As a matter of responsibility, MSME managers are required to report their activities and performance results every month so that they know the profits and losses of their MSMEs. But the managers have not carried out reporting as a form of their responsibility. Based on the background description that has been stated, this assistance activity is entitled "Assistance in Preparing Profit and Loss Reports for Micro, Small and Medium Enterprises (Mumkm) at the Apoh Tahu Factory"